Efficient separation and comprehensive extraction of aluminum, silicon, and iron from coal fly ash by a cascade extraction method. (20th June 2023) - Zhao, Xiaodan; Zeng, Li; Guo, Jiaming; Zhu, Qiaoling; Huang, Zhuojun; Lin, Lifeng; Chen, Xuanang; Cao, Jing; Zhou, Zhen
Abstract: A cascade extraction method was constructed by combining alkali desilication with carbonation and acid leaching to achieve efficient separation and comprehensive recovery of aluminum, silicon, and iron products in coal fly ash (CFA). Alkaline desilication obtained the maximum SiO2 extraction efficiency of 65.7% after response surface methodology optimization, transformed mullite phase to hydroxysodalite [Na8 Al6 Si6 O24 (OH)2 (H2 O)2 ], and generated fiber-formed nanostructures, which were beneficial for resource extraction. After being treated by dosing Ca(OH)2 to recover CaSiO3 crystal, the supernatant of desilication was recycled to reduce alkali consumption and waste liquid discharge. The desilicated CFA was activated by carbonate calcination to convert mullite into the nepheline phase, thereby elevating the dissolution efficiency of Al2 O3 and Fe2 O3 to 90.4% and 92.3% by acid leaching. Acid leaching also converted silicious compounds in activated CFA to silicic acid with a purity of 93.9%. Stepwise precipitation obtained Fe(OH)3 and Al(OH)3 products with purities of 70.6% and 90.8%. The generated CaSiO3, silica gel, Fe(OH)3, and Al(OH)3 can be recycled as flame retardants, and the recovered Al(OH)3 could be converted to NaAlO2 for chloride removal from saline wastewater. The cascade extraction is economically beneficial and environmentally friendly without solid waste production for utilization of CFA. Graphical abstract: Image 1 Highlights: Al, Si, and Fe in coal fly ash (CFA) were recovered by a cascade extraction method. Alkaline desilication separated Si from CFA and converted mullite to hydroxysodalite. Acid leaching after carbonate calcination extracted Al and Fe and yielded silica gel. The process recovered CaSiO3, silica gel, Fe(OH)3, and Al(OH)3 without solid waste. The cascade extraction method is cost-efficient and harmless for CFA utilization.